2015
DOI: 10.1007/s11051-014-2815-2
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of cerium oxide nanoparticles and its influence on functions of mouse leukemic monocyte macrophages

Abstract: Exposure of the CeO 2 nanoparticles (NPs) causes a public concern on their potential health risk due to their wide applications in the fields of fuel additive, commodities, pharmaceutical, and other industries. In this study, the interactions between two commercial CeO 2 NPs (D-CeO 2 from Degussa and PC-CeO 2 from PlasmaChem) and mouse leukemic monocyte macrophage Raw264.7 cells were investigated to provide a fast and in-depth understanding of the biological influences of the NPs. Both types of the CeO 2 NPs h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Hence, various pharmacological inhibitors (amantadine, genistein, amiloride and cytochalasin D) were used. Amantadine prevented the budding of clathrin-coated pits; genistein retarded the activation of the Src family of tyrosine kinases; amiloride inactivated Na + /H + channels; and cytochalasin D destroyed the cytoskeleton to inhibit NP transportation [ 40 ]. Figure 2 d showed that cytochalasin D significantly suppressed the internalization efficiency of ZnCM NPs compared to amantadine, genistein and amiloride after 2 h of incubation, indicating the feasible participation of the DC cytoskeleton in the process of ZnCM NP ingestion, which was independent of clathrin-caveolin-mediated endocytosis.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, various pharmacological inhibitors (amantadine, genistein, amiloride and cytochalasin D) were used. Amantadine prevented the budding of clathrin-coated pits; genistein retarded the activation of the Src family of tyrosine kinases; amiloride inactivated Na + /H + channels; and cytochalasin D destroyed the cytoskeleton to inhibit NP transportation [ 40 ]. Figure 2 d showed that cytochalasin D significantly suppressed the internalization efficiency of ZnCM NPs compared to amantadine, genistein and amiloride after 2 h of incubation, indicating the feasible participation of the DC cytoskeleton in the process of ZnCM NP ingestion, which was independent of clathrin-caveolin-mediated endocytosis.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the extraneous particles may evoke some inflammatory cells such as monocytes to migrate to the affected area and differentiate into macrophages or dendritic cells, triggering immune response . RAW264.7 cells, which are undifferentiated mononuclear macrophage with a strong phagocytic ability and a potential to initiate immune response, have been widely used in the in vitro model to study the toxicity and inflammatory response of nanomaterials. , Therefore, A549 lung epithelial cells and RAW264.7 cells were assayed in terms of viability and inflammatory response challenged by PM2.5 and remedied by PPADT NPs.…”
Section: Resultsmentioning
confidence: 99%
“…59 RAW264.7 cells, which are undifferentiated mononuclear macrophage with a strong phagocytic ability and a potential to initiate immune response, have been widely used in the in vitro model to study the toxicity and inflammatory response of nanomaterials. 60,61 Therefore, A549 lung epithelial cells and RAW264.7 cells were assayed in terms of viability and inflammatory response challenged by PM2.5 and remedied by PPADT NPs.…”
Section: Resultsmentioning
confidence: 99%